Simultaneous high strength and mechanical stability of bcc Nb/Mg nanolaminates. (1st January 2023) - Jain, Manish; Yaddanapudi, Krishna; Kidigannappa, Anugraha Thyagatur; Baldwin, Kevin; Knezevic, Marko; Mara, Nathan A.; Beyerlein, Irene J.; Pathak, Siddhartha
Abstract: While bimetallic nanocomposites have demonstrated extraordinary – three to even ten-fold – gains in strength with decreasing layer thickness, their strengths tend to plateau beyond a critical layer thickness. More disappointingly, such increases in strength are almost always accompanied by a decrease in their strains to failure (ductility). In this work we report simultaneous improvements in both strength and mechanical stability of Nb/Mg nanolaminates with decreasing layer thicknesses, a trend seldom reported in nanolaminates consisting of pure metals. Using micro-pillar compression and nanoindentation experiments we show that physical vapor deposited (PVD) Nb/Mg nanolaminates that contain a body center cubic (bcc) Mg pseudomorphic phase demonstrate a >60% increase in strength and a >80% increase in strain to failure over those containing the hexagonal close packed (hcp) Mg phase. Instead of a strength plateau, the hcp-to-bcc phase transition in Mg results in a renewed strengthening regime in the nanolaminate caused by the change to a coherent interface from an incoherent one, along with a concurrent increase in strain-to-failure due to the introduction of a more plastically isotropic bcc material from an anisotropic hcp structure. Using high resolution transmission electron microscopy (HR-TEM) we also demonstrate the presence of a thin layer of bcc Mg at the Nb/Mg interface at larger layer thicknesses when Mg is predominantly hcp. Our results suggest that the increases in strain to failure in the Nb/Mg nanolaminates with decreasing layer thicknesses can be corelated to the approximate volume fraction of the pseudomorphic bcc Mg present in the layers. Graphical abstract: Image, graphical abstract